(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Today, concrete is one of the most important and widely used products of human production. Improving the properties of concrete has always been one of the main issues facing structural engineers. Improving the physical properties of water, as one of the main elements of concrete, is one of the ways to improve the properties of concrete. Concrete with magnetic water resistance is called water that it has passed through the magnetic field and its physical quality has changed. Today, in special structures, for example, tall structures that require high pressure, it is not possible to provide the required strength by increasing the aggregate and cement, as a result, materials that are fully compatible with concrete materials and environments and improve compressive strength are needed. Structures that require high compressive strength and at the same time high rebar density, cannot increase the water to cement ratio to achieve the required performance, because it causes a sharp drop in compressive strength. Therefore, to solve this problem (achieving high resistance and efficiency), additives are examined and used. In this research, magnetic water analysis on structural and non-structural concretes has been investigated using multi-criteria decision making method, according to the experiments, magnetic water increases the compressive strength of 28 days by 28% and increases the slump of concrete by 30%, also, using the results of statistical tests such as Friedman test, magnetic water can be considered as one of the main components of concrete, also, using the results of the tests, the main priorities in the formation of structural and non-structural concrete and the expectations we have from structural and non-structural concrete were obtained.